The effect of practising chess on working memory and strategic thinking among students of the University of Babylon (Journal of Humanities and Social Sciences Research, 2026)
This study aims to examine the effectiveness of a chess training program in developing working memory and enhancing strategic thinking among students of the University of Babylon. The researcher adopted an experimental method using a two-group design (experimental and control). The experimental group underwent a training program consisting of 16 sessions distributed over eight weeks, while the control group continued their usual activities without training. Measurement instruments were employed after verifying their validity and reliability. The results revealed statistically significant differences in favour of the experimental group in the post-test, with large effect sizes, confirming that practising chess within a structured program can contribute to the development of cognitive and analytical abilities among students who practice chess.